Two-Phase Approach to the Nesting problem with continuous rotations. Issue 3 (2015) - Rocha, Pedro; Rodrigues, Rui; Gomes, A. Miguel; Toledo, Franklina M.B.; Andretta, Marina
Abstract: This paper presents an approach that assists in producing highly compacted Nesting layouts with irregular pieces using free rotations. This approach consists in the selection and compaction of big pieces in a first phase, while in a second phase, places the remaining small pieces between the big pieces, compacting all of them. The effect of several parameters are analyzed, such as minimum length to be achieved in the first phase, attraction of the pieces to the edges of the container, attraction between each pair of pieces, among others. This approach can provide good compaction results, while improving computational cost in some cases, which can allow to tackle real world problems more effectively and efficiently.